2022
DOI: 10.18280/mmep.090625
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Analysis in a Lid-Driven Square Cavity with Hemispherical Obstacle in the Bottom

Abstract: Incompressible fluid flow research uses lid-driven cavity as a benchmark issue to measure computer simulation accuracy. Flow within a hollow includes recirculation, turbulence, eddies, instability, impingement, flow separation, attachment with walls (moving and stationary), fluid entrapment in the recirculation area, and other fluid flow phenomena. In this article, forced convection in a lid-driven square cavity with a sliding top wall and hemispherical obstruction is mathematically illustrated. This chamber f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Friction factor can be predicted by the use of the subsequent empirical correlation [41][42][43][44][45][46]:…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…Friction factor can be predicted by the use of the subsequent empirical correlation [41][42][43][44][45][46]:…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…Figure (2-a) presents the mesh distribution of the proposed model. figure (3-a) is a mesh shapes and distribution of rectangular container filled with phase-changing materials is studied without rode, while in figure (3-a) , longitudinal rods mesh, and figure (3-a) , rods of v shape [ 26 , 28 , 29 ].
Fig.
…”
Section: Numerical Proceduresmentioning
confidence: 99%
“…This observation demonstrates grid independence, indicating that the calculated results were not significantly affected by the choice of mesh density. The mesh with the lowest element count (22,701) was carefully chosen for subsequent simulations since it had a faster computing time. This choice ensured that computational efficiency was maximized while maintaining accuracy standards.…”
Section: Grid Independence and The Code Validationmentioning
confidence: 99%
“…Increasing the inner HTF tubes caused an acceleration in the melting process, and enhanced heat transport with the addition of the nanoparticle was experimentally tested. Several studies have demonstrated that adding nanoparticles to PCM improves heat transport, shortening the time for the melting process to complete [21,22]. Other studies conducted experiments in which nanofluids were added to PCMs as a new phase to investigate their effect on a material's capacity for thermal energy storage [23,24].…”
Section: Introductionmentioning
confidence: 99%